ГДЗ решебник по алгебре 7 класс Л.И. Звавич, Л.В. Кузнецова

Вариант 2

с-30

 

1. 1) a) (1-4x)/4 = 1; 1 - 4x = 5; 4х = -4; x = -1;
6) (3x-10)/2 = -1; 3x - 10 =-2; 3x = 8; x = 2 2/3;
в) (x+3)/10 = 1/5; x + 3 = 2; x = -1;
2) a) (8x+3)/7 = (10x-1)/7; 8x + 3 = 10x - 1; 2x = 4; x = 2;
6) (x+2)/5 = (3x-5)/4; 4(x + 2) = 5(3x - 5); 4x + 8 = 15x - 25
11x = 33; x = 3;
в) (7-x)/6 = (19x-11)/8; 4(7 - x) = 3(19x - 11);
28 - 4x = 57x - 33; 61x = 61; x = 1;
3) а) (5x-9)/4 + (5x-7)/4 = 1;
5х - 9 + 5х - 7 = 4;
10x = 20;
х = 2;
б) 2х - (2x+3)/3 = (x-6)/3;
6x - 2х - 3 = x - 6;
3x = -3;
х = -1;
в) (2-x)/5 - x/15 = 1/3;
3(2 - x) - x = 5; 
6 - 3х - х = 5; 
4х = 1; x = 0,25;
г) x/7 - (3x-1)/14 = 2
2x - 3х + 1 = 28;
x = -27;
д) (2x-3)/9 + (x-1)/5 = 2;
5(2x - 3) + 9(x - 1) = 90; 
10x - 15 + 9x - 9 = 90; 
19x = 114;
x = 6;
e) (x+14)/5 - (6x+1)/7 = 1;
7(x + 14) - 5(6x + 1) = 35;
7x + 98 - 30x - 5 = 35; 
23x = 58;
x = 2 12/23.

2. 1) (5x-4)/3 + (3x-2)/6 + (2x-1)/2 = 3x - 2;
2(5x - 4) + 3x - 2 + 3(2x - 1) = 6(3x - 2);
10x - 8 + 3x - 2 + 6х - 3 = 18x - 12; х = 13 - 12 = 1;
2) (2x-3)/5 + (x-1)/4 + (5x+1)/20 = 3 - x;
4(2х - 3) + 5(х - 1) + 5x + 1 = 20(3 - x);
8x - 12 + 5x - 5 + 5x + 1 = 60 - 20x; 38x = 76; x = 2;
3) x2 - 5x + 3 - (3x2-5x-7)/3 = 1/3;
3(х2 - 5х + 3) - 3x2 + 5x + 7 = 1;
3x2 - 15x + 9 - 3х2 + 5х + 7 = 1;
10x = 15; x = 1,5.